Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

log x - log 6 = 2 log 4


Sagot :

log(x) - log(6) = 2 log(4)

Condense the left side, using the property log(a) - log(b) = log(a/b) (if b ≠ 0):

log(x / 6) = 2 log(4)

Rewrite the right side, using the property n log(a) = log(aⁿ ):

log(x / 6) = log(4²)

log(x / 6) = log(16)

Cancel the logarithms (i.e. take the exponential of both sides):

exp(log(x / 6)) = exp(log(16))

x / 6 = 16

Solve for x :

x = 6 × 16

x = 96